Forecasting The Growth of Manufacturing Industry in Malaysia Using Artificial Neural Network - Zakaria, Norzaini (2006)
An Artificial Neural Network (ANN) formulation for forecasting the growth of manufacturing industries in Malaysia is presented. The effectiveness of ANN for predicting one criterion, Y form several predictors, X, is investigated. Comparative studies are examined between the result of the predictions from the ANN model trained with Multi-Layer Feed forward Perception, a Generalised Regressions Neural Network (GRNN) algorithm and the result obtained from traditional statistical approach.